P098 Predicting delays in or failure to initiate CPAP therapy: A retrospective cohort study. (7th October 2021) - Moore, S; Duce, B; Ellender, C; Hukins, C
Abstract: Background: Suboptimal CPAP usage is associated with negative outcomes and inefficient use of medical resources. Demographic and polysomnographic characteristics are well established predictors of poor adherence, however the literature regarding patients who fail to initiate treatment is limited. This audit aimed to identify features associated with the delayed commencement or failure to initiate CPAP therapy. Methods: A single institution, retrospective cohort study was performed. The cohort comprised adults with obstructive sleep apnoea prescribed CPAP between 2017 and 2018. The demographic, clinical and polysomnographic features of this cohort were identified. Comparisons were conducted between patients who initiated therapy and those who did not, as well as between early and delayed initiators of treatment, which was defined as uptake after one month. Multiple logistic regression was performed with significance defined as a p<0.05. Results: 916 patients were identified. 38.2% of patients did not uptake prescribed CPAP, with male gender (p < 0.001), younger age (p=0.007) and lower pressure (p=0.016) identified as prognostic factors. Socioeconomic disadvantage (p=0.774) and Epworth Sleepiness Scale (p=0.111) were not associated with failure to start treatment. Of the 61.8% of patients who initiated CPAP therapy, 33% exhibited a delayed start to therapy, with indigenous status a significant feature of this cohort (p=0.002). Discussion: A large portion of patients displayed either delayed commencement or failure to initiate CPAP therapy. Younger age, male gender and lower prescribed pressures were identified as negative predictive factors. These characteristics, as well as delayed treatment experienced in the indigenous population, provide focus points for intervention.